VICTOR DEUPI, JEAN-FRANCOIS LEJEUNE - Cuban Modernism. Mid-Century Architecture 1940-1970 - Gómez Díaz, Francisco (ZARCH, 2022)
Victor Deupi, Jean-Francois Lejeune Cuban Modernism. Mid-Century Architecture 1940-1970Basilea: Birkhäuser Verlag GmbH., 2021. 334 pp. Tapa dura. 48 €ISBN-10‏: ‎ 3035616418ISBN-13: ‎ 978-3035616415